Disulfiram treatment suppresses antibody-producing reactions by inhibiting macrophage activation and B cell pyrimidine metabolism - Weili Chen; Etsuko Toda; Kazuhiro Takeuchi; Yurika Sawa; Kyoko Wakamatsu; Naomi Kuwahara; Arimi Ishikawa; Yuri Igarashi; Mika Terasaki; Shinobu Kunugi; Yasuhiro Terasaki; Kazuhiko Yamada; et al. (Communications Biology, 2024)
Abstract Antibody responses, involving B cells, CD4 + T cells, and macrophages, are implicated in autoimmune diseases and organ transplant rejection. We have previously shown that inhibiting FROUNT with disulfiram (DSF) suppresses macrophage activation and migration, effectively treating inflammatory diseases. In this study, we investigated the effectiveness of DSF in antibody-producing reactions. Using a heart transplantation mouse model with antibody-mediated rejection, we administered anti-CD8 antibody to exclude cellular rejection. DSF directly inhibited B cell responses in vitro and significantly reduced plasma donor-specific antibodies and graft antibody deposition in vivo, resulting in prolonged survival of the heart graft. DSF also mediated various effects, including decreased macrophage infiltration and increased Foxp3+ regulatory T-cells in the grafts. Additionally, DSF inhibited pyrimidine metabolism-related gene expression induced by B-cell stimulation. These findings demonstrate that DSF modulates antibody production in the immune response complexity by regulating B-cell and macrophage responses.